The Harvest Ritual in North Central Mindanao - Madigan, Francis C. (Sociological analysis, 1964)
The ritual system of the rural people of Misamis Oriental and the northern half of Bukidnon Province extends to almost all aspects of life. The kinship complex, the debt-repayment complex, and the spirit-world complex bind the rituals in enduring fashion into the culture of the area. Chief among the commonly practiced food-production rituals is the harvest ritual. This consists principally of a spirit meal at which appropriate vocal prayers to the spirits are improvised by the ritual leader. Because the obligation of offering the meal is believed to be grave, most farm families carefully fulfill it each year. Solutions to the pastoral problems raised by the existence and practice of the rituals by Catholics are not likely to be found in proscribing their performance by Catholics, but in further study of the nature and functions of the rituals.